Dentine biomarkers of prenatal and early childhood exposure to manganese, zinc and lead and childhood behavior. (December 2018) - Horton, Megan K.; Hsu, Leon; Claus Henn, Birgit; Margolis, Amy; Austin, Christine; Svensson, Katherine; Schnaas, Lourdes; Gennings, Chris; Hu, Howard; Wright, Robert; Rojo, Martha María Téllez; Arora, Manish
Abstract: Background: Metal exposure alters neurodevelopmental outcomes; little is known about critical windows of susceptibility when exposure exerts the strongest effect. Objective: To examine associations between dentine biomarkers of manganese (Mn), zinc (Zn) and lead (Pb) and later childhood behaviors. Methods: Subjects enrolled in a longitudinal birth cohort study in Mexico City provided naturally shed deciduous teeth. We estimated weekly prenatal and postnatal dentine Mn, Zn and Pb concentrations in teeth using laser ablation-inductively coupled plasma-mass spectrometry (LA-ICP-MS) and measured behavior at ages 8–11 years of age using the Behavior Assessment System for Children, 2nd edition (BASC-2). We used distributed lag models and lagged weighted quantile sum regression to identify the role of individual and combined dentine biomarkers of Mn, Zn and Pb on behavioral outcomes controlling for maternal education and gestational age. Results: Among the 133 subjects included in this study, prenatal and early postnatal dentine Mn appeared protective against childhood behavioral problems, specifically hyperactivity and attention. Postnatal dentine Mn was associated with increased reporting of internalizing problems, specifically anxiety. At 6 months, a 1-unit increase (unit = 1 SD of log concentration) in Mn was associated with a 0.18-unit (unit = 1 SD of BASC-2 score) increase in internalizing symptoms score and a 0.25-unit increase in anxiety. Postnatal Pb was associated with increasing anxiety symptoms; at 12 months, a 1-unit increase in Pb was associated with a 0.4 unit increase in anxiety symptoms. When examined as a metal mixture, we observed two potential windows of susceptibility to increased anxiety symptoms: the first window (0–8 months) appeared driven by Mn, the second window (8–12 months) was driven by the metal mixture and dominated by Pb. A 1-unit increase in the mixture index was associated with a 0.7-unit increase in SD of anxiety symptoms. Conclusions: Childhood behaviors may demonstrate postnatal windows of susceptibility to individual and mixed metal concentrations measured in deciduous teeth. Prenatal dentine Mn may be protective, while excessive early postnatal Mn may increase risk for adverse behaviors. In combination, higher concentrations of Mn, Zn and Pb may have an adverse impact on behavior. Highlights: Tooth-matrix biomarkers were used to identify windows of susceptibility to Mn, Zn, and Pb. Prenatal and early postnatal Mn appears protective against externalizing behavior. Postnatal Mn is associated with higher internalizing behaviors, especially anxiety. Co-exposure to Mn, Zn and Pb at 12 months is associated with anxiety.